(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
Firms must face up, earlier and earlier, the need to internationalize. Provided that it is very difficult that firms possess all the necessary resources, capabilities and competencies to internationalize, strategic alliances for the internationalization appear as one of the most valid instruments through which firms can face up its internationalization. However, the study of cooperative agreements for the internationalizationis scarce. In this paper we analyze the main scientific contributions with the purpose of detecting possible dark points that need to be studied in major depth.